ANALISIS TINGKAT KERUSAKAN PADA BANGUNAN GEDUNG SEKOLAH DASAR NEGERI DI KOTA SUKABUMI - Hidayatullah, Ilham (Peneliti.net, 2024)
School building is the main component of supporting teaching and learning and becomes one of the determining factors for improving the quality of an educational institution. The availability of facilities and infrastructure is an important element as a support for the success of the education and teaching process in the school environment, so that proper maintenance and maintenance are needed in the use of the building. In the process of its use, many school buildings are not maintained due to the lack of attention of the school to the quality of the building, so a lot of damage is done to the school building. One of the efforts in dealing with damaged buildings is with renovation and rehabilitation, to determine the handling of it requires assessment of damage assessment on school buildings first through direct surveys, then continued with analysis of the extent of damage to get data on Minor Damage (RR), Moderate Damage (RS), and Severely Damaged (RB). The results of research from 100 elementary schools in Sukabumi City consisting of 7 districts that suffered damage were 92 schools, from classrooms getting lightly damaged (RR) 12%, moderately damaged (RS) 75%, and heavily damaged (RB) 13%, Lightly Damaged Library (RR) 33%, Moderately Damaged (RS) 47%, and Severely Damaged (RB) 20%, teacher room / Lightly Damaged Kepsek (RR) 13%, Moderately Damaged (RS) 80%, and Severely Damaged (RB) 7%, WC Lightly Damaged (RR) 10%, Moderately Damaged (RS) 64%, and severely damaged (RB) 26%, rung UKS Lightly Damaged (RR) 13%, Moderately Damaged (RS) 73%, and Severely Damaged (RB) 14%. From the assessment above, it can be concluded that classrooms and wc must be repaired immediately because they are needed.